Shaping of a High-Frequency Dynamic Loading of Members of the Running Gear of a Tracklaying Vehicle - V.B. Derzhansky; I.A. Taratorkin (Механика машин, механизмов и материалов, 2010)
The assaying of conditions of excitation and stability of parametric vibrations of basic running rollers of a high-speed tracklaying vehicle is resulted at interacting with a rubber racetrack of a caterpillar. Experimentally it is installed, that parametric vibrations restrict longevity of elements of the running gear, reduces efficiency of operation of the high-precision equipment of a tracklaying vehicle, raise calorific intensity of tyres of basic running rollers. Functions of a legitimate value of parametres of modulation of a rigidity and a running speed from a relationship of frequencies disturbing and characteristic are defined.